The impact of the COVID-19 pandemic on lifestyle patterns: Does gender matter? - Sultana, Naznin; Asaduzzaman, Md.; Mubarak, Mahfuza; Hosen, Ismail; Kaggwa, Mark Mohan; Al-Mamun, Firoj; Mamun, Mohammed A. (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic has significantly impacted individuals to deviate from normal lifestyle behaviors. But, there is a paucity of studies conducted in Bangladesh assessing how lifestyle patterns (i.e., smoking, drug use, physical exercise) have changed after the pandemic, which was investigated in this study. Methods: An online-based cross-sectional survey was conducted among a total of 756 Bangladeshi young adults between April 1 and 13, 2020. Lifestyle patterns data were collected based on two periods from the COVID-19 pandemic inception point in the country, (i) ‘one year before’, and (ii) ‘one year after’. Basic descriptive statistics (i.e., frequency and percentages) and Chi-square tests were performed to examine the associations of the independent variables in relation to lifestyle patterns. Results: A 0.2% and 4.7% reduction in smoking and physical exercise, respectively, was observed after the pandemic. But the prevalence of drug use was 1.5% before the COVID-19 pandemic, which rose to 1.9% during the pandemic; representing a 0.4% increment. The changes in lifestyle patterns before and during the COVID-19 pandemic was statistically significant only for physical exercise. Of the gender, male participants were more prevalent in smoking, drug use, and performing physical exercise in both periods. Conclusion: It is suggested to increase awareness concerning adverse effects of drug use and not performing physical exercise, where the gender-based focus is highly appreciated.